Aging Invisibly : Championing Diversity in Scholarship on Growing Older with Chronic Illness - Nowakowski, Alexandra Xan" C.H.",; Sumerau, J.E., (Educational Research E-Books Online, Collection 2024., 2024)
Statistical data suggest that many people with chronic health conditions pass away at much younger ages than their peers. Yet large quantitative datasets that address aging with chronic illness often do not capture the diversity of people with c